فاعليه‌ تمارين توافقية في تحسين مستوى التوافق وبعض انواع التصويب في كرة السلة - عبدلله, خالد حسين (Sulaimani Journal for Humanities, 2018)
The basketball games practiced categorize a small area of the stadium, which requires the player to own high level of skills and motor abilities physical elements through which can a player to continue to play and compete, and all of these components requires the player Correlation. between the parties and different parts of the body Ani able to continue play So Correlation is one of the important abilities that need to training coaches in basketball, and its fundamental role in the performance of basic skills, including the shooting. Through informed researcher categorize Platform coaches of the Federation of basketball in the region, the difference is the omission of this important capability. And not to give the exercises a consensual mixed exercises and exercises . Pearls without considering the privacy of this ability from here it emerged the idea of research in an experimental scientific study COORDINTED exercises with the ball and some kind of correction in basketball. مجلة )زانکۆی سلێمانی( القسم )B )للدراسات االنسانیة – العدد )65( عدد خاص لمؤتمر الدولي األول لكلیة التربیة الرياضية 899 The subjects search for the second phase of the School of Physical Education students - Koya University for the academic year 2015-2016 totaling 59 students, were selected sample of 20 students from the same stage . Which form the forgotten (50%) of the original research community Done implement major test on Thursday, 03.03.2016 until 26.04.2016 by two units a week for eight weeks and a total of 16 units. Where they are taking special lecture basketball are given exercises harmonic main section of the lesson as it has been focusing more and COORDINTED exercises with the use of the ball in most of the exercises.